If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4n + 73 = 5 Reorder the terms: 73 + 4n = 5 Solving 73 + 4n = 5 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-73' to each side of the equation. 73 + -73 + 4n = 5 + -73 Combine like terms: 73 + -73 = 0 0 + 4n = 5 + -73 4n = 5 + -73 Combine like terms: 5 + -73 = -68 4n = -68 Divide each side by '4'. n = -17 Simplifying n = -17
| 4x+6=-54-8 | | 3y=15-x | | -77=-++55 | | =(3-2)X+2Y+2 | | y=3.40x+2.20 | | 2x-4=86 | | ln(2x)-ln(3)=5 | | 3x+17=11x+47 | | 6x+106=2x+108 | | -2n^2+9=-7n | | =X+2Y+2 | | n-13=86 | | a^2-6a=9 | | c-28=51 | | -2x^2=-2-3x | | 35/7=p | | 3b-4/2 | | -21=9a-15-3 | | 7=g/8 | | 6b-(5-4b)=25 | | 3(x-3)+6=4x+3 | | -21=9a-15 | | 4x+2(10-x)=28 | | (a^2b^-3)^3a^2b/a(2b)^-3 | | 12x+5=5x+20 | | 12-9m=-4(-6m-3) | | x^2=11k-28 | | 4(8p-9)=-3(-12p+8) | | L=ml | | 2h+3-12h=9(-h+2) | | 12+5=7x-4 | | 9.7s+1.56=10.9s |